Réponses

Meilleure réponse !
2013-11-10T15:25:36+01:00
Bonjour

I = - (3x² +7) +6x-1 - (15x²+7x-3)
= -3x² -7 +6x -1 - 15x² -7x +3
= -18x² -x -4
pour x = 1
A = -18 -1-4 = -23

J = x² -3x² +15x -4 +15x² -12x² -x
= x² +14x -4
pour x = 1, A = 1 +14 -4 = 9

A = 3x+6 -x +1 = 2x +7
B = 12x +4 -4x -7 = 8x -3
C = 7x -21 +3x +6 +2x -2 = 12x  -17

A = 3x -2 -5(2x -1) = 3x -2 -10x +5 = -7x +3

A = x² -5x -6 -2x = x² -7 x -6
pour x = 1 , A = 1 -7 -6 = -12
B = -6x² -12x -2x + 3x² = -3x² -14x
pour x = 1 , B = -9 -14 = - 23
C = 3x² -21 +6x -1 - 15x -35x² -3 = -32x² - 9x -25
pour x = 1, C = -1024 - 9 -25 = - 1058
merci mais il faut que je détaille si vous pouvez m'aidez merci